Two new species of notodasus fauchald, 1972 (Annelida: Capitellidae) from the Central Indo-Pacific region - Lin, Jun Hui; García Garza, María Elena; Arbi, Ucu Yanu; Wang, Jian Jun (PeerJ Inc., 2019)
Notodasus Fauchald, 1972 is a small genus of the polychaete family Capitellidae, including 10 described species worldwide. The genus is unusual in the Central IndoPacific, and there is no taxonomic record of Notodasus in this region. In this study, two new species of Notodasus are described and illustrated, namely Notodasus celebensis sp. nov. and N. chinensis sp. nov. The former species, collected from the mixed-species seagrass beds in the Indonesian island of Sulawesi, is mainly characterized by the longitudinally striated epithelium on thoracic segments and the completely separated notopodial lobes. The latter species, obtained from coastal waters off southern China, differs from its congeners with the following characters: tessellated epithelium present on anterior thorax as well as on the dorsum of chaetigers 11 and 12, notopodial lobes fused and chaetal fascicles almost touching each other on anterior abdomen, and branchial pores evident from anterior abdomen. Comparisons are made with closely related species in this paper, and a revised key is provided to all described Notodasus species. The descriptions of the two new species represent the first record of Notodasus in this region and expand the geographical distribution of the genus.